The Effect of Patriarchical Culture and Glass Ceiling on Teacher Career Development Mediated by Career Opportunities in Kindergarten Teachers in South Cikarang District, Bekasi Regency - Jubaedah, Jubaedah; Setyaningrum, Retno Purwani (Majapahit Journal of Islamic Finance and Management, 2025)
Career development is a hope for workers everywhere, any position, including as a teacher. The purpose of this study was to analyze the influence of Patriarchal Culture and Glass Ceiling on Teacher Career Development mediated by Career Opportunities in Kindergarten Teachers in South Cikarang District, Bekasi Regency. This study uses a quantitative method, the respondents with a population of 134 and a sample using the slovin formula obtained a sample of 100 respondents. Data collected through questionnaires distributed using Google Form. Data management is carried out using Partial Least Square (PLS) through the Structural Equation Model (SEM) technique with the help of the SmartPLS version 4.1.1 program. The results of the analysis obtained are that Patriarchal Culture has a significant effect on Teacher Career Development, Glass Ceiling has a significant effect on Teacher Career Development, Career Opportunities do not have a significant effect on Teacher Career Development, Patriarchal Culture has a significant effect on Career Opportunities, Glass Ceiling does not have a significant effect on Career Opportunities. In addition, career opportunities are not able to mediate the influence of Patriarchal Culture on teacher career development, and career opportunities are not able to mediate the influence of Glass Celling on teacher career development.